(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Stroke or cerebrovascular accident is a leading cause of death and disability especially in the elderly population. The prognosis depends upon the early detection, extent of injury and the level of repair occurring within the CNS. Underlying pulmonary and cardiac risk factors like history of smoking, hypertension specifically have a significant effect on the development of poststroke aspiration pneumonia. Complications similar to these delay the path to rehabilitation significantly exposing the patient to the risks of prolonged immobilization, introduction of artificial airways for ventilation and development of secondary complications like pressure sores. In this case report, we aim to document the strategies applied for the complete rehabilitation of the individuals from the acute setting all the way till the rehabilitation in spite of hemodynamic instabilities to help professionals dealing with similar patients.